2022
DOI: 10.3389/fmars.2022.976019
|View full text |Cite
|
Sign up to set email alerts
|

Plasticity in the morphometrics and movements of an Antarctic apex predator, the leopard seal

Abstract: Animals that display plasticity in behavioral, ecological, and morphological traits are better poised to cope with environmental disturbances. Here, we examined individual plasticity and intraspecific variation in the morphometrics, movement patterns, and dive behavior of an enigmatic apex predator, the leopard seal (Hydrurga leptonyx). Satellite/GPS tags and time-depth recorders were deployed on 22 leopard seals off the Western Antarctic Peninsula. Adult female leopard seals were significantly larger (454±59 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 99 publications
0
12
0
Order By: Relevance
“…For example, a recent study by Feyrer et al (2020) using stable isotope analysis of teeth showed that lactation durations of northern bottlenose whales (Hyperoodon ampullatus) were 3 to 4 years instead of the previous best estimate of at least 1 year, which was a minimum estimate based on the presence of milk and prey in the stomach of a one-year old calf (Benjaminsen and Christensen, 1979). Satellite telemetry data from a single leopard seal (Hydrurga leptonyx), a species where lactation durations are unconfirmed but speculations range from 10 days to 8 weeks (Southwell et al, 2003), provides preliminary support for a 2-week lactation duration (Kienle et al, 2022). In North Atlantic right whales, the use of genetic identification revealed that at least two calves never observed on the foraging grounds with their mothers survived, indicating successful weaning as early as 7.5 to 8.0 months of age on the northbound migration (Hamilton et al, 2022) A particular challenge in estimating total lactation costs is that there is a high degree of intraspecific variation in lactation durations in some species.…”
Section: Lactation Durationmentioning
confidence: 87%
“…For example, a recent study by Feyrer et al (2020) using stable isotope analysis of teeth showed that lactation durations of northern bottlenose whales (Hyperoodon ampullatus) were 3 to 4 years instead of the previous best estimate of at least 1 year, which was a minimum estimate based on the presence of milk and prey in the stomach of a one-year old calf (Benjaminsen and Christensen, 1979). Satellite telemetry data from a single leopard seal (Hydrurga leptonyx), a species where lactation durations are unconfirmed but speculations range from 10 days to 8 weeks (Southwell et al, 2003), provides preliminary support for a 2-week lactation duration (Kienle et al, 2022). In North Atlantic right whales, the use of genetic identification revealed that at least two calves never observed on the foraging grounds with their mothers survived, indicating successful weaning as early as 7.5 to 8.0 months of age on the northbound migration (Hamilton et al, 2022) A particular challenge in estimating total lactation costs is that there is a high degree of intraspecific variation in lactation durations in some species.…”
Section: Lactation Durationmentioning
confidence: 87%
“…Despite being a top predator, recent studies have shown broad intraspecific variability with regard to diet, which is quite diverse and varies seasonally [68]. Variability is also observed in diving behavior [69], hunting strategies [70], the use of ice floes [71] and movements [29]. In fact, the traditional notion that leopard seals are exclusively found in the Antarctic has also recently been rejected [19].…”
Section: Effective Population Size Vs Census Sizementioning
confidence: 99%
“…To date, published genetic analyses of leopard seals are limited [25,26] and descriptions of key demographic parameters such as N E are lacking. [27,28] and can disproportionally impact ecosystems [29]. For example, leopard seals have consumed an estimated 69.3% of all Antarctic fur seal pups (Arctocephalus gazella) born annually at Cape Shirreff in the north Antarctic peninsula since 2010, contributing to the rapid collapse of this regional population [28].…”
Section: Introductionmentioning
confidence: 99%
“…As leopard seals (Hydrurga leptonyx), rāpoka | popoiangore | poipopiangori | popoikore (hereafter 'leopard seals') are primarily found in the remote Antarctic pack ice and sub-Antarctic Islands (Laws 1977;Rogers 2013), the effects of climate change on sea ice (including pack ice) may have considerable implications for their activity (Meade et al 2015). External tracking devices applied to the pelage, such as glued tags, have assisted in monitoring leopard seal activity (Rogers et al 2005;Krause et al 2016;Kienle et al 2022), but their usage is limited by the loss and replacement of pelage during the annual moult (e.g. Rogers et al 2005;Kienle et al 2022).…”
Section: Introductionmentioning
confidence: 99%
“…External tracking devices applied to the pelage, such as glued tags, have assisted in monitoring leopard seal activity (Rogers et al 2005;Krause et al 2016;Kienle et al 2022), but their usage is limited by the loss and replacement of pelage during the annual moult (e.g. Rogers et al 2005;Kienle et al 2022).…”
Section: Introductionmentioning
confidence: 99%